2022
DOI: 10.3390/nu14040913
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Metabolic Imbalance in Keratoconus

Abstract: Keratoconus (KC) is a progressive corneal degeneration characterized by structural changes consisting of progressive thinning and steepening of the cornea. These alterations result in biomechanical weakening and, clinically, in vision loss. While the etiology of KC has been the object of study for over a century, no single agent has been found. Recent reviews suggest that KC is a multifactorial disease that is associated with a wide variety of genetic and environmental factors. While KC is typically considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…A gender-related difference is believed to play an important role in changes in corneal tissue structures ( 27 30 ). Male patients account for a higher proportion than female patients based on previous investigations of adult keratoconus ( 7 , 9 , 10 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gender-related difference is believed to play an important role in changes in corneal tissue structures ( 27 30 ). Male patients account for a higher proportion than female patients based on previous investigations of adult keratoconus ( 7 , 9 , 10 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Males have higher levels of androgens, while females have a higher estrogen level ( 34 , 35 ). The cornea expresses multiple receptors and enzymes for sex hormone metabolism and cellular activities, which further bind to sex hormones, leading to hormonal level changes and further causing other anatomic and physiological differences between males and females ( 9 , 30 , 36 ). In addition, the male/female ratio decreased with age in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted mass spectrometry analysis of human serum from a small case–control study revealed increased dehydroepiandrosterone sulfate and prostaglandins in patients with KC compared to age-matched controls [ 85 ], which is consistent with a study by our group [ 86 ] and others [ 87 , 88 ] associating altered hormone levels or their receptors with KC. Growing evidence supports the hypothesis that there is a systemic component involved in KC pathogenesis upstream of the endogenous oxidative stress observed in the cornea [ 89 , 90 ].…”
Section: Corneamentioning
confidence: 89%
“…Previous studies demonstrated the importance of vitamins in maintaining ocular surface homeostasis, suggesting the possible protective effects against damages ( Lasagni Vitar et al, 2022 ). Vitamins are essential for many corneal functions and help ensuring corneal integrity supporting the epithelial barrier and cells survival ( Yin et al, 2011 ; Bucolo et al, 2015 ; Reins et al, 2015 ; Gozzo et al, 2021 ; Kaminska et al, 2021 ; Lasagni Vitar et al, 2022 ). Moreover, their anti-inflammatory, antimicrobial and antioxidant properties have been demonstrated ( Wimalawansa, 2019 ).…”
Section: Discussionmentioning
confidence: 99%